2009
DOI: 10.1590/s1806-83242009000100004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the time required for removal of intraradicular cast posts using two Brazilian ultrasound devices

Abstract: The aim of this in vitro study was to compare the time required for removal of intraradicular cast posts cemented with zinc phosphate (ZF) or glass ionomer cement (GIC), using two Brazilian ultrasound devices (BUD). Seventy two human inferior premolars with single root canals were sectioned transversally at the cementoenamel junction. In each specimen, the root canal was endodontically treated, the post space was prepared to a depth of 9 mm and the canal was molded to obtain a post impression. After the castin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
2
15
0
2
Order By: Relevance
“…Although in vitro tests are not always able to reproduce in vivo conditions, they can offer comparative values that may guide clinical procedures. 18 When an ultrasonic device is used for post removal, the vibration is transferred to the cement line by the post. Thus, the vibration is expected to cause the cement to fracture and facilitate the post removal procedure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although in vitro tests are not always able to reproduce in vivo conditions, they can offer comparative values that may guide clinical procedures. 18 When an ultrasonic device is used for post removal, the vibration is transferred to the cement line by the post. Thus, the vibration is expected to cause the cement to fracture and facilitate the post removal procedure.…”
Section: Discussionmentioning
confidence: 99%
“…19 Several factors may interfere in the ultrasonic efficiency, such as the type of luting agent, length, form, diameter and type of post and post adaptation to the root canal walls. 8,17,18,20,21 The efficacy of ultrasound is related to the intensity and movement of the vibration, the manner in which the tip is applied on the core and the type of tip used. …”
Section: 16mentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have suggested the use of ultrasound alone or in combination with other techniques to make this procedure safer. [37]…”
Section: Introductionmentioning
confidence: 99%